Humoral and cellular responses to mRNA vaccines against SARS-CoV-2 in patients with a history of CD20 B-cell-depleting therapy (RituxiVac): an investigator-initiated, single-centre, open-label study. (November 2021) - Moor, Matthias B; Suter-Riniker, Franziska; Horn, Michael P; Aeberli, Daniel; Amsler, Jennifer; Möller, Burkhard; Njue, Linet M; Medri, Cesare; Angelillo-Scherrer, Anne; Borradori, Luca; Radonjic-Hoesli, Susanne; Seyed Jafari, S Morteza; et al.
Abstract: Background: B-cell-depleting therapies increase the risk of morbidity and mortality due to COVID-19. Evidence-based SARS-CoV-2 vaccination strategies for patients on B-cell-depleting therapies are scarce. We aimed to investigate humoral and cell-mediated immune responses to SARS-CoV-2 mRNA-based vaccines in patients receiving CD20-targeted B-cell-depleting agents for autoimmune disease, malignancy, or transplantation. Methods: The RituxiVac study was an investigator-initiated, single-centre, open-label study done at the Bern University Hospital (Bern, Switzerland). Patients with a treatment history of anti-CD20-depleting agents (rituximab or ocrelizumab) and with no previous history of SARS-CoV-2 infection were enrolled between April 26 and June 30, 2021, for analysis of humoral and cell-mediated immune responses (by interferon-γ [IFNγ] release assay) at least 4 weeks after completing vaccination against SARS-CoV-2. Healthy controls without a history of SARS-CoV-2 infection were also enrolled at least 4 weeks after completing vaccination against SARS-CoV-2. All study participants received two doses of either the Pfizer–BioNTech BNT162b2 vaccine or the Moderna mRNA-1273 vaccine. The primary outcome was the proportion of patients with a history of anti-CD20 treatment who showed a humoral immune response against the SARS-CoV-2 spike protein in comparison with immunocompetent controls. Prespecified secondary endpoints were the effect of anti-CD20 therapy (including time since last treatment and cumulative dose) on humoral or cell-mediated immune responses to SARS-CoV-2 vaccination, and biomarkers of immunocompetence. This study is registered with ClinicalTrials.gov, NCT04877496 . Findings: The final study population comprised 96 patients and 29 immunocompetent controls. The median age of patients was 67 years (IQR 57–72) and of controls was 54 years (45–62), and 51 (53%) of 96 patients and 19 (66%) of 29 controls were female. The median time since last anti-CD20 treatment was 1·07 years (IQR 0·48–2·55) and the median cumulative dose of an anti-CD20 depleting agent was 2·80 g (1·50–5·00). Anti-spike IgG antibodies were detected in 47 (49%) of 96 patients 1·79 months (IQR 1·16–2·48) after the second vaccine dose compared to 29 (100%) of 29 controls 1·81 months (1·17–2·48) after the second vaccine dose (p<0·001). SARS-CoV-2-specific IFNγ release was detected in 14 (32%) of 44 patients and 22 (88%) of 25 healthy controls (p<0·001). Only ten (23%) of 44 patients were double positive for anti-SARS-CoV-2 spike IgG and cell-mediated responses, compared with 22 (88%) of 25 healthy controls (p<0·001). Time since last anti-CD20 therapy (>7·6 months; positive predictive value 0·78), peripheral CD19 + cell count (>27 cells per μL; positive predictive value 0·70), and CD4 + lymphocyte count (>653 cells per μL; positive predictive value 0·71) were predictive of humoral vaccine response (area under the curve [AUC] 67% [95% CI 56–78] for time since last anti-CD20 therapy, 67% [55–80] for peripheral CD19 + count, and 66% [54–79] for CD4 + count). Interpretation: This study provides further evidence of blunted humoral and cell-mediated immune responses elicited by SARS-CoV-2 mRNA vaccines in patients with a history of CD20 B-cell-depleting treatment. Lymphocyte subpopulation counts were associated with vaccine response in this highly vulnerable population. On validation, these results could help guide both the administration of SARS-CoV-2 vaccines and B-cell-depleting agents in this population. Funding: Bern University Hospital.